Analisis Pengaruh Likuiditas dan Profitabilitas Terhadap Harga Saham Industri Jasa - Naura Hasna Nafia; Yacobo P Sijabat (The Academy Of Management and Business, 2022)
The service industry is needed by investors as an investment opportunity because the service industry becomes dominant as the economy develops. In this study, the Current Ratio (CR), Earnings Per Share (EPS), Return On Assets (ROA), and Return On Investment (ROI) are all examined in relation to stock prices. SPSS software version 24 and descriptive research with a quantitative approach were used in this study. The results showed that the hypothesis test of multiple linear regression analysis with independent variables (Current Ratio, Earning Per Share, Return On Investment, and Return On Equity) and one dependent variable, namely stock prices, explained that the Current Ratio (CR), Return on Assets (ROA), and Return on Investment (ROI) have no significant effect on stock prices, but Earning Per Share (EPS) has a significant effect on stock prices.